An Alternative to Representation: Explaining Preferences for Citizens as Political Decision-Makers. (August 2019) - Gherghina, Sergiu; Geissel, Brigitte
Extensive scholarly attention is devoted to citizens' preferences for alternative models of political decision-making. However, few efforts were made to identify who these citizens are and why they display a certain preference. To address this void in the literature, our article analyzes the determinants of preferences for citizens as decision-makers. It uses individual-level data from a 2014 survey on a probability representative sample in Germany and tests the effects of political attitudes toward institutions of representative democracy, interest in politics, and civic involvement. It controls for consumption of political news, education, and age.